2021
DOI: 10.1038/s41598-021-03049-6
|View full text |Cite
|
Sign up to set email alerts
|

The improved grasshopper optimization algorithm and its applications

Abstract: Grasshopper optimization algorithm (GOA) proposed in 2017 mimics the behavior of grasshopper swarms in nature for solving optimization problems. In the basic GOA, the influence of the gravity force on the updated position of every grasshopper is not considered, which possibly causes GOA to have the slower convergence speed. Based on this, the improved GOA (IGOA) is obtained by the two updated ways of the position of every grasshopper in this paper. One is that the gravity force is introduced into the updated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Different from particle swarm optimization (PSO), the grasshopper optimization algorithm (GOA) is a group-based nature-inspired calculation method. The updating of the search agent positions is affected by the position of each search agent, allowing the GOA to effectively achieve gradual and balanced exploration of the search space when searching for the optimal results [29,30]. Therefore, the GOA is a suitable method for solving the proposed UFLS model.…”
Section: Solution Methods For the Ufls Modelmentioning
confidence: 99%
“…Different from particle swarm optimization (PSO), the grasshopper optimization algorithm (GOA) is a group-based nature-inspired calculation method. The updating of the search agent positions is affected by the position of each search agent, allowing the GOA to effectively achieve gradual and balanced exploration of the search space when searching for the optimal results [29,30]. Therefore, the GOA is a suitable method for solving the proposed UFLS model.…”
Section: Solution Methods For the Ufls Modelmentioning
confidence: 99%
“…Recent years have witnessed the potential use of GOA in the field of science and engineering like multi-objective test problems, image processing, scheduling, machine learning, and motion tracking [2528]. However, several variants of GOA approaches are suggested to overcome the gaps in GOA [29,30]. The combination of Bees algorithm (BA) and GOA has been proposed to address the deployment problem in WSN [31].…”
Section: Related Workmentioning
confidence: 99%
“…In traditional GOA, it can be observed that the effect of gravity force while updating the position of the grasshopper is not considered. In [30], the authors introduced a gravity force while updating the position of each grasshopper in the traditional GOA. The following arithmetic model is used to show the updated position of the grasshoppers.…”
Section: (∑ (| |) )mentioning
confidence: 99%
“…Yi Feng et al 20 (2020) introduced Dynamic Opposite Learning assisted GOA for the Flexible Job Scheduling Problem. Qin, P et al 21 (2021) have successfully applied improved GOA to optimise the parameters of the BP neural network for predicting the closing prices of the Shanghai Stock Exchange Index and the air quality index (AQI) of Taiyuan, Shanxi Province.…”
Section: Introductionmentioning
confidence: 99%